The Catechism of the Catholic Church: An Appraisal - Buckley, Francis J. (Horizons, 1993)
The format is a scholastic treatment of creed, sacraments, morality, and prayer with many allusions to Scripture, church Councils, and teachings of the magisterium, particularly in the social teachings of the church. This Catechism could have been written before the Second Vatican Council with references to Council documents added later, much as the biblical references were added as "proof-texts." The biblical, liturgical, ecumenical, and catechetical movements have not had a substantial impact on the structure or content of the Catechism. There are many excellent features of the Catechism. It avoids the question-and-answer format. It dropped the major doctrinal errors. Its expanded development of prayer is superb. The greatest weakness of the Catechism is its steadfast refusal to distinguish teachings of the magisterium which demand an assent of faith from teachings which demand some other interior assent.